Can parents who smoke socialise their children against smoking? Results from the Smoke-free Kids intervention trial. Issue 1 (1st March 2003) - Jackson, C; Dickinson, D
Abstract : Objective: To evaluate Smoke-free Kids, a new home based programme to assist parents who smoke in socialising their children against smoking. Design: Two year randomised controlled trial. Participants: At baseline, 887 adult smokers who had an abstinent child in the third grade (ages 7–8 years); 671 adults and children were retained through the 24 month follow up. Intervention: Programme modules, newsletters, incentives, support calls. Outcomes: Anti-smoking socialisation; susceptibility to smoking. Results: Of 327 parents randomised to treatment, 210 obtained adequate treatment by using at least three of five core modules. Programme efficacy analyses, which compared these parents with controls (n = 344), showed that exposure to adequate treatment predicted significantly higher levels in nearly all categories of anti-smoking socialisation three months post-intervention. Two years post-baseline, children of parents who reported adequate treatment scored significantly higher than controls on attributes that reduce susceptibility to smoking, and they scored significantly lower than controls on attributes that raise susceptibility to smoking. Programme effectiveness analyses compared all parents randomised to treatment (n = 327) with controls (n = 344). Treatment effects were evident for several socialisation outcomes; however, these effects were smaller and less consistent than those from the efficacy analyses. Similarly, although treated children scored higher than controls on attributes that reduce susceptibility and lower than controls on attributes that raise susceptibility, several of these between-group differences were not significant. Conclusions: Given adequate exposure to the Smoke-free Kids programme, significant beneficial effects were observed on anti-smoking socialisation in households where parents smoke cigarettes, and significant beneficial effects were observed on children's susceptibility to smoking after two years. Improving programme acceptance and utilisation is necessary before programme effectiveness can be demonstrated.